2022
DOI: 10.1039/d2nj01358d
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrochemical sensor for determination of uric acid in the presence of ascorbic acid and dopamine based on a carbon paste electrode modified with an electrochemically reduced para-nitrobenzoic acid/graphene oxide nanocomposite

Abstract: In this study, a highly sensitive electrochemical sensor based on a carbon paste electrode was modified by an electrochemically reduced para-nitrobenzoic acid/graphene oxide nanocomposite to measure uric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The ZnO NR-CuO NS/GC sensor showed 0.5 μM (S/N = 3) limit of detection. Table shows a comparative sensing performance of different sensors, where we can see that our fabricated sensor showed better sensing performance. ,, Such boosted sensing performance could be attributed to the ZnO NR-CuO NS hybrid nanostructure, where electro-active sites may be present in abundance. However, the enzymeless UA catalysis over the working electrode surface having nanomaterials is not well reported in the literature.…”
Section: Results and Discussionmentioning
confidence: 91%
“…The ZnO NR-CuO NS/GC sensor showed 0.5 μM (S/N = 3) limit of detection. Table shows a comparative sensing performance of different sensors, where we can see that our fabricated sensor showed better sensing performance. ,, Such boosted sensing performance could be attributed to the ZnO NR-CuO NS hybrid nanostructure, where electro-active sites may be present in abundance. However, the enzymeless UA catalysis over the working electrode surface having nanomaterials is not well reported in the literature.…”
Section: Results and Discussionmentioning
confidence: 91%
“…Nitrobenzoic acid and its derivatives are essential materials in pharmaceutical industries [ 14 , 15 , 16 ]. A literature study revealed a good deal of work on the properties of NBA and its substituted derivatives [ 17 ].…”
Section: Nitrobenzoic Acid (Nba)mentioning
confidence: 99%
“…On the other hand, electrochemical-based sensors have the potential for rapid detection and offer high-sensing performance during biomolecules detection [ 8 , 9 , 10 , 12 , 13 , 14 ]. Recently, considerable attention has been given to electrochemical-based UA sensors due to their high selectivity, accuracy, less interference, and low-cost [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of electrodes (i.e., metal-based and carbon-based electrodes) that are mostly used in electrochemical sensor fabrication. The carbon-based electrodes (i.e., glassy carbon, screen-printed, and carbon-paste electrodes) are the preferred working electrodes due to the minimum over potential requirement compared to the metal-based electrodes [ 19 ]. Due to their low costs and ease of preparation, the carbon-based electrodes have been extensively used in electrochemical sensing applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation